Serum-Mediated Oxidative Stress from Systemic Sclerosis Patients Affects Mesenchymal Stem Cell Function - Fonteneau, Guillaume; Bony, Claire; Goulabchand, Radjiv; Maria, Alexandre T. J.; Le Quellec, Alain; Rivière, Sophie; Jorgensen, Christian; Guilpain, Philippe; Noël, Danièle (Frontiers in Immunology, 2017)
Objectives: Properties of mesenchymal stem cells (MSCs) from Systemic Sclerosis (SSc) patients have been reported to be altered. MSC-based therapy relies on the use of allogeneic MSCs from healthy subjects. Here, we investigated whether heterologous MSCs could exhibit altered properties following exposure to oxidative environment of SSc sera. Methods: Human bone marrow-derived MSCs were cultured in presence of various sera: control human serum AB (SAB), SAB with HOCl-induced AOPPs at 400 or 1000 µmol/L (SAB400, SAB1000) or H2O2-induced AOPPs or SSc patient serum (PS). Proliferation, apoptosis, senescence rates of MSCs were evaluated after 3, 6 and 10 days in culture. ROS and NO production were quantified at 24h. Trilineage potential of differentiation was tested after 21 days in specific culture conditions and immunosuppressive function measured in a T lymphocyte proliferative assay. Results: In presence of oxidative environment of SSc sera, MSCs retained their proliferative potential and survived for at least the first 3 days of exposure, while the number of senescent MSCs increased at day 6 and apoptosis rate at day 10. Exposure to SSc sera enhanced the anti-oxidant capacity of MSCs, notably the expression of SOD2 antioxidant gene. By contrast, the osteogenic/adipogenic potential of MSCs was increased whereas their immunosuppressive function was slightly reduced. Discussion: Although some functional properties of MSCs were affected upon culture with SSc sera, evidence from pre-clinical studies and the present one suggested that MSCs can adapt to the oxidative environment and exert their therapeutic effect.